The Radio Sky and How to Observe It - Lashley, Jeff.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
We have learned a great deal about our universe not only by looking at the sky through optical telescopes but also by listening to it! Although in the past most of the great discoveries have been made by professional radio astronomers using large radio telescopes built for institutions, today even amateurs can build and use small radio telescopes and make discoveries that can contribute to the general store of knowledge. And you don$1 (Bt need to be an electronics genius or rich! Jeff Lashley, in this comprehensive guide to the science and art of putting together and using a small radio telescope, will lead you through the process and help you to understand what to listen for. Filled with projects and tips and great advice, he can get you underway in a hurry and help you to decode what you are hearing. So if you$1 (Bve been doing amateur astronomy for a while and want to expand beyond what you can see with your eyes, this is a direction you should consider going in. Or, if you$1 (Bve dabbled in building radios for years and want to try something new, this can be a way to expand your hobby. Either way, start now listening to the fireworks going on all around you$1 (Byou$1 (Bll be amazed!s
The Radio Sun -- Jupiter -- Meteors and Meteor Streams -- Beyond the Solar System -- Antennae -- Setting Up a Radio Astronomy Station -- Radio Hardware Theory -- to RF Electronics -- Building a Very Low Frequency Solar Flare Monitor -- Microwave Radio Telescope Projects -- Building a Jupiter Radio Telescope -- Building a Broad Band Solar Radio Telescope -- Data Logging and Data Processing.
Keywords: Science (General).; Astronomy; Popular Science; Popular Science in Astronomy; Astronomy, Observations and Techniques